Law, Ethics, and Constitutional Morality: Lessons from Indonesia and the United States of America - Fradhana Putra Disantara; Geraldha Islami Putra Disantara; Dinara F. Abdunayimova (University of Jember, Indonesia, 2025)
This study examines the development of legal reforms in strengthening constitutional morality, constitutional ethics, and the rule of law in Indonesia and the United States, with an emphasis on the different approaches taken by the two countries based on their respective legal systems. This research is normative legal research with a conceptual, comparative, and legislative approach. The research findings confirm that in Indonesia, constitutional morality and ethics are considered to require special regulation in law as a formal effort to provide legitimacy and normative binding force within the national legal system, given that these values have not yet become naturally ingrained outside of written rules. Conversely, in the United States, the strengthening of constitutional morality and ethics is more often realised through judicial mechanisms, specifically through the dynamic and responsive rulings of the Supreme Court, where judicial review serves as the primary instrument for interpreting and enforcing moral and ethical values as an integral part of living legal practice. This study confirms that the effectiveness of legal updates in strengthening constitutional morality and ethics is highly dependent on the foundation of each country's legal system. Therefore, Indonesia needs to focus on strengthening legal formality, while the United States utilises the strength of its judicial institutions as guardians and developers of ethical and moral values within the constitution. This finding confirms the importance of contextual legal updates as key to making constitutional morality and ethics not just normative concepts, but practically realised in national life in order to achieve clean, democratic, and just governance.